El delito de abuso de poder económico en el Perú: desafios en su tipificación como delito y en el estándar probatorio en sede administrativa - Vinelli Vereau, Renzo (2025)
The crime of abuse of economic power in Peru has undergone a fluctuating regulatory evolution, reflecting the tension between criminal intervention and administrative regulation in economic matters. Its criminalization, currently contained in article 232 of the Criminal Code, responds to the need to punish anticompetitive practices of absolute prohibition. In this context, the competence of INDECOPI to previously establish the existence of an administrative infringement introduces a referral mechanism that conditions the criminal prosecution.